Addressing interpersonal patterns in patients with personality disorders partially explains psychotherapy outcome via changes in interaction patterns: A mediation analysis. (17th November 2022) - Babl, Anna; Berger, Thomas; Eubanks, Catherine F.; Gómez Penedo, Juan Martín; Caspar, Franz; Sachse, Rainer; Kramer, Ueli
ABSTRACT: Objective Many patients with personality disorders (PDs) present with problematic interaction patterns. These may also manifest in the therapeutic relationship. For successful treatment, therapists must therefore find effective ways to address such problematic interaction patterns. Methods: A total of 382 patients with PDs were recruited within a naturalistic setting and received integrative cognitive–behavioral therapy (CBT). Two subscales of the observer-rated Process-Content-Relationship Scale were applied to sessions 15, 20, and 25 of treatment: one on patient interaction patterns and the other on therapist addressing these. Symptom severity was assessed at intake and discharge. Mediation analysis was applied. Results: We found significant main effects of (1) therapists' addressing problematic interaction patterns in session 15 on patients' changes in such patterns from session 15 to 25 and (2) patients' changes in problematic interaction patterns on symptom severity at treatment termination. Further, the effect of therapists' addressing problematic interaction patterns on outcome was mediated by changes in patients' interaction patterns. Conclusion: The results indicate that therapists' addressing of PD patients' problematic interaction patterns may be particularly important to improve such patterns and thereby treatment outcome. Future research should identify in which patients the mechanism of addressing interaction patterns works best.